ANALYSIS OF THE SUSTAINABLE DEVELOPMENT OF THE OF THE CITY OF GUANAMBI IN THE LIGHT OF DWORKIN THEORY OF EQUALITY (CIPEEX, 2022)
THE PRESENT STUDY AIMS TO ANALYZE SUSTAINABLE DEVELOPMENT FROM THE THEORY OF DWORKIN'S (2008) RESOURCE EQUALITY, HAVING AS OBJECT OF STUDY THE URBAN PERIMETER OF GUANAMBI, A CITY LOCATED IN THE SEMI-ARID REGION OF BAHIA, WITH AN APPROXIMATE URBAN POPULATION OF 62,565 INHABITANTS (IBGE, 2010). THE PRESENT WORK IS JUSTIFIED BY THE SCIENTIFIC NEED TO STUDY AND KNOW THE URBAN CONTEXT OF THE CITY OF GUANAMBI, THE EFFECTIVENESS OR NOT OF THE URBAN LEGAL SPECTRUM, THE LEGAL AND REAL APPLICABILITY OF THE PRINCIPLE OF SUSTAINABLE DEVELOPMENT TO CITIES AND EQUALITY AMONG CITIZENS, IN ORDER TO PRODUCE LOCAL KNOWLEDGE ABOUT THE CONFIGURATION OF THE OBJECT OF STUDY, FACILITATING THE STRATEGIC DIRECTION IN THE PROMOTION OF PUBLIC POLICIES THROUGH POLITICAL ENTITIES AND PRODUCERS OF URBAN SPACE. TO OPTIMIZE THE ELABORATION OF THE WORK, THE RESEARCH WAS DIVIDED INTO FIVE STAGES, AS FOLLOWS: (A) METHODOLOGY, EXPOSING THE MATERIALS AND THE METHODOLOGICAL CONSTRUCT USED FOR THE PRODUCTION OF THIS ONE, IN ORDER TO SUBSIDIZE SIMILAR RESEARCH; (B) THE FULL DEVELOPMENT OF CITIES AND THE FUNDAMENTAL RIGHT TO SUSTAINABLE CITIES, MAKING BRIEF COMMENTS ABOUT THE TEMPORAL FRAMEWORK OF THE PRINCIPLE AND ITS CONSTITUTIONAL FOUNDATION; (C) THE THEORY OF EQUALITY IN DWORKIN AND THE SUSTAINABLE DEVELOPMENT OF CITIES; (D) ANALYSIS OF SUSTAINABLE DEVELOPMENT IN THE CITY OF GUANAMBI IN THE LIGHT OF THE DWORKINIAN THEORY, AND FINALLY (E) FINAL CONSIDERATIONS ABOUT THE RESULTS OBTAINED.
Keywords: Urban Development; Right to the City; Public Policies